An empirical analysis of the effect of business incubation process on firm performance in Nigeria. (2nd November 2017) - Iyortsuun, Akuraun Shadrach
Abstract : Small and medium enterprises (SME), acknowledged as tools of economic development, are faced with size-related challenges. Governments around the world design institutions to support them. Business incubation is one of such frameworks for entrepreneurial promotion and SME development. This study predicts firm performance from the constructs of the business incubation process: selection performance, business assistance intensity, resource munificence and professional management services. Using hierarchical multiple regression, the overall model was significant explaining 13.5% of the variation in firm performance with a moderate effect size. Business assistance intensity and professional management services were significant predictors while incubator selection performance and resource munificence were not significant predictors of firm performance. Incubation should be promoted as a tool for entrepreneurial promotion to complement the broader strategic entrepreneurial framework for entrepreneurship promotion. The focus should be on evolving strategies to expand and deepen incubators capacity by intensifying business assistance and professional management services to their clients.